From: album in archive Vollmar, nr3869, nr.89. Letter to Georg v. Vollmar, dated 1883, February 22, on the back - Kuijer, W.G.,
From: album in archive Vollmar, nr3869, nr.89. Letter to Georg v. Vollmar, dated 1883, February 22, on the back.